Establishing the efficacy of interventions to improve health literacy and health behaviours: a systematic review - Ronie Walters; Stephen J. Leslie; Rob Polson; Tara Cusack; Trish Gorely (BMC, 2020)
Abstract Background The primary aim of this review was to establish whether health literacy interventions, in adults, are effective for improving health literacy. Two secondary aims assessed the impact of health literacy interventions on health behaviours and whether health literacy interventions have been conducted in cardiovascular patients. Methods A systematic review (Prospero registration: CRD42018110772) with no start date running through until April 2020. Eligible studies were conducted in adults and included a pre/post measure of health literacy. Medline, Embase, Eric, PsychINFO, CINAHL, Psychology and Behavioural Science, HMIC, Web of Science, Scopus, Social Care Online, NHS Scotland Journals, Social Policy and Practice, and Global Health were searched. Two thousand one hundred twenty-seven papers were assessed, and 57 full text papers screened to give 22 unique datasets from 23 papers. Risk of bias was assessed regarding randomisation, allocation sequence concealment, blinding, incomplete outcome data, selective outcome reporting and other biases. Intervention reporting quality was assessed using the TIDieR checklist. Results Twenty-two studies were included reporting on 10,997 participants in nine countries. The majority of studies (14/22) were published in 2018 or later. Eight studies (n = 1268 participants) also reported on behavioural outcomes. Health literacy interventions resulted in improvements in at least some aspect of health literacy in 15/22 studies (n = 10,180 participants) and improved behavioural outcomes in 7/8 studies (n = 1209 participants). Only two studies were conducted with cardiovascular patients. All studies were at risk of bias with 18 judged as high risk. In addition, there was poor reporting of intervention content with little explication of the theoretical basis for the interventions. Conclusions Health literacy interventions can improve health literacy and can also lead to changes in health behaviours. Health literacy interventions offer a way to improve outcomes for populations most at risk of health inequalities. Health literacy is a developing field with very few interventions using clear theoretical frameworks. Closer links between health literacy and behaviour change theories and frameworks could result in higher quality and more effective interventions. Prospero registration Prospero registration: CRD42018110772